The Utilization of Media Advertising of Giant Supermarket as an Information Source - Erna Mariana Susilowardhani; Bida Sari (Atma Jaya Indonesia Catholic University, Jakarta, 2015)
The increasing number of supermarkets in the capital city of Jakarta, causing supermarkets have been competing to attract consumers. They make a variety of media advertising. One is Giant Supermarket. But, the consumers differ in the way of getting information as a reference from the media advertising of Giant Supermarket. Therefore, in this study, researchers want to know the consumers experience in utilization of media advertising which is made by Giant Supermarket as a source of information for them. This study use the concepts of marketing communications. Some of the concepts are the concept of promotion, promotional mix, advertising, media advertising: above the line and below the line. Researchers use a qualitative-descriptive approach. Researchers use a type of primary data and secondary data. For primary data, researchers conduct observation and in-depth interviews to a number of informants. For secondary data, researchers conduct a literature review and documentation. Researchers use an authenticity as a technique of data validity. The results obtained, that among consumers, they utilize different of media advertising as a source of information for them. They were relying on information from the catalog, banners, or advertising in newspapers. Each medium has less and also more benefits according to the informants. Things to be noted by the Giant Supermarket is related to the availability of the product being promoted between the products are listed in media advertising and the products are existed in Giant Supermarket itself.